2007
DOI: 10.1086/522875
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicity among Young Brown Dwarfs and Very Low Mass Stars

Abstract: We report on a near-infrared adaptive optics imaging survey of 31 young brown dwarfs and very low mass ( VLM) stars, 28 of which are in the Chamaeleon I star-forming region, using the ESO Very Large Telescope. We resolve the suspected 0:16 00 ($26 AU ) binary Cha H 2 and present two new binaries, Hn 13 and CHXR 15, with separations of 0:13 00 ($20 AU ) and 0:30 00 ($50 AU ), respectively; the latter is one of the widest VLM systems known. We find a binary frequency of 11 þ9 À6 %, thus confirming the trend for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 49 publications
6
58
0
Order By: Relevance
“…DM91 found that G dwarfs tend to have lower mass companions (with a modal mass ratio of q ∼ 0.3), while surveys of M dwarfs by FM92 and RG97 found a flat distribution and several recent surveys of brown dwarfs (e.g., Close et al 2003;Burgasser et al 2003;Bouy et al 2003) found that their mass ratios are sharply peaked toward unity. By contrast, surveys of young associations have found that flat mass ratio distributions seem to dominate across a range of system masses, from ∼2 M to at least as low as 0.5 M (e.g., for Upper Sco), though a distribution biased toward unity seems to be universal among the lowest mass stars and brown dwarfs (Kraus et al 2006;Ahmic et al 2007).…”
Section: The Mass Ratio Distribution Of Wide Binariesmentioning
confidence: 86%
“…DM91 found that G dwarfs tend to have lower mass companions (with a modal mass ratio of q ∼ 0.3), while surveys of M dwarfs by FM92 and RG97 found a flat distribution and several recent surveys of brown dwarfs (e.g., Close et al 2003;Burgasser et al 2003;Bouy et al 2003) found that their mass ratios are sharply peaked toward unity. By contrast, surveys of young associations have found that flat mass ratio distributions seem to dominate across a range of system masses, from ∼2 M to at least as low as 0.5 M (e.g., for Upper Sco), though a distribution biased toward unity seems to be universal among the lowest mass stars and brown dwarfs (Kraus et al 2006;Ahmic et al 2007).…”
Section: The Mass Ratio Distribution Of Wide Binariesmentioning
confidence: 86%
“…Such small separation can have a strong impact on the disk (see e.g., Bitner et al 2010), and may explain why the disk is not detected at PACS wavelengths. However, out the of five M5 stars with known multiplicity, two of them are detected with the Herschel data even at small separation: objects #6 (28.9 separation, Kraus & Hillenbrand 2007) and #15 (0.13 separation Ahmic et al 2007;Lafrenière et al 2008). It does not seem (based on five sources) that binarity can solely explain the low detection rate of M5 stars in the Herschel map of Cha-I.…”
Section: Detection Statistics and Probabilitiesmentioning
confidence: 95%
“…Manoj et al (2011, and references therein) reported that five M5 stars in Cha I are in multiple systems, some of them having small separations. For instance 0.17 separates the primary and secondary of the Cha Ha2 system (Ahmic et al 2007;Lafrenière et al 2008) corresponding to about 28 AU at 165 pc. Such small separation can have a strong impact on the disk (see e.g., Bitner et al 2010), and may explain why the disk is not detected at PACS wavelengths.…”
Section: Detection Statistics and Probabilitiesmentioning
confidence: 99%
“…(13) supposed by Neuhäuser et al (2002). (14) confirmed by Ahmic et al (2007), Lafrenière et al (2008) and Schmidt et al (2008b). (15) Schmidt et al (2008b).…”
Section: Introductionmentioning
confidence: 91%
“…(8) Neuhäuser et al (2002). (9) see also Ahmic et al (2007) and Lafrenière et al (2008). (10) Brandner (1992).…”
Section: Rx J11094-7627mentioning
confidence: 99%